If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(3p + -6) = 192 Reorder the terms: -8(-6 + 3p) = 192 (-6 * -8 + 3p * -8) = 192 (48 + -24p) = 192 Solving 48 + -24p = 192 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + -24p = 192 + -48 Combine like terms: 48 + -48 = 0 0 + -24p = 192 + -48 -24p = 192 + -48 Combine like terms: 192 + -48 = 144 -24p = 144 Divide each side by '-24'. p = -6 Simplifying p = -6
| 4-3a/4 | | y+8=-2(x+0) | | 28=2(x+4) | | -10=-4x-4 | | 5a-20=180 | | 4x-2/3=70/3 | | -2x+2z+3y= | | ln(x)=5.4+ln(6.5) | | 3x+6x-4x= | | f(x)=x^2+18x+60 | | -4x-18=-34 | | =12a^2b^6 | | 10x-8=-28 | | 3a+8=180 | | 4x*18+2x*6=248 | | -(4r-7)=2-5r | | 13-2+2x=x+3 | | 1.25d+3.25=1+2.25d | | x(3.5)=2.5 | | -5(-9-6)=15 | | 2.3=1/2y | | x^2+6x=573 | | -4x-18=-30 | | x^2+6x=5743 | | 6x-2(3x-5)=154 | | -66y-45x+10(7-123x)=1520 | | 2x^2+8x+x+9=0 | | 40+8x=8*5+8*x | | 8x+10=10x-5 | | 7z+5+9=-16 | | 5n^2+12n-5=0 | | x/9=43 |